Comparison of clinical and electrophysiological characteristics between ictal and cardiac asystole encountered during video‐EEG monitoring. Issue 4 (23rd August 2019) - Sankaranarayanan, Muthukani; Makhija, Prashant; Gopinath, Siby; Mathew, Navin; Radhakrishnan, Kurupath
ABSTRACT: Aims . Differentiation between syncope secondary to epileptic seizures and cardiac disease in patients displaying transient loss of consciousness associated with convulsive movements is a diagnostic challenge both for neurologists and cardiologists. In such patients, prolonged video‐EEG monitoring not only helps in identifying asystole as the cause of syncope, but also in categorizing asystole as primarily cardiac in origin (cardiac asystole) and secondary to epileptic seizures (ictal asystole). We carried out this study to ascertain the prevalence of asystole in an epilepsy monitoring unit, and to contrast the clinical and electrophysiological characteristics between ictal asystole and cardiac asystole. Methods . Through a retrospective search, we identified patients who were shown to have had asystole using a database of patients who underwent prolonged video‐EEG monitoring during a 68‐month period. We compared the data of 18 consecutive patients; five with ictal asystole and 13 with cardiac asystole, with 121 and 64 events recorded from them, respectively. Results . Of the 10, 096 patients who underwent prolonged video‐EEG monitoring during the study period, we identified 18 (0.17%) patients with asystole. Cardiac asystole was 2.6 times more frequent than ictal asystole. Older age at onset, heralding symptoms of presyncope, occurrence during wakefulness, and brief duration of the events supported the diagnosis of cardiac asystole. Ictal asystole events were more protracted, and prolonged asystole more frequently occurred in patients with extratemporal seizures compared to temporal lobe seizures. Asystole occurred in only half of the recorded seizures. Conclusions . The accurate categorization of asystole as seizure‐related or heart disease‐related has huge implications for management strategy and outcome. The necessity of permanent pacemaker implantation is more frequent and urgent in patients with cardiac asystole because of the greater risk of sudden death. Hence, in patients with an ominous diagnosis of cardiac asystole, a thorough cardiac evaluation should surpass neurological evaluation.